A method for manufacturing a titanium-zirconium-niobium alloy by selective laser melting

CN118268593BActive Publication Date: 2026-10-13XI AN JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410360214.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2026-10-13
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

[0004]针对现有技术中选取激光熔化时存在致密度较低以及飞溅等导致钛锆铌合金成型困难的问题,本发明提供一种选区激光熔化技术制备钛锆铌合金的方法

Benefits of technology

[0023]本发明一种选区激光熔化技术制备钛锆铌合金的方法中选用了对人体基本无毒副作用的锆、铌两元素进行材料复合,通过选区激光熔化技术的快速凝固特点,得到更加精细的微观结构,同时引入一定量的位错,从而能够显著提升钛锆铌合金的强度,并保持了较好的塑性。在满足使用性能的同时保证使用安全性,采用选区激光熔化技术解决了现有技术中成型致密度较低的问题,拓展钛锆铌合金的加工制备路线。相较于熔炼制备,本发明中由于激光的瞬时温度较高,因此会在熔池内部形成较高的温度梯度,因此制得样品晶粒尺寸更小,根据晶体强化理论的细晶强化,强度会随着晶粒降低而增强;其次,会在晶粒内部形成一定量得位错堆积,在受力时位错开动受阻,从而提升强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118268593B_ABST
    Figure CN118268593B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of titanium alloy material preparation, and particularly relates to a method for preparing a titanium-zirconium-niobium alloy by using a selective laser melting technology, which comprises the following steps: S1, weighing alloy powder; S2, filling the alloy powder in a top powder cabin, laying the alloy powder on a printing substrate, and then cleaning a printing chamber until the oxygen content in the chamber is less than 0.02%; S3, using a Z-shaped scanning mode of a laser to perform layer-by-layer printing on the alloy powder to obtain a titanium-zirconium-niobium alloy sample. In the present application, the two elements of zirconium and niobium, which have no toxic side effects on human bodies, are selected to be compounded into a material, and through the rapid solidification characteristics of the selective laser melting technology, a more fine microstructure is obtained, and a certain amount of dislocation is introduced, so that the strength of the titanium-zirconium-niobium alloy can be significantly improved, and good plasticity is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium alloy material preparation technology, specifically a method for preparing titanium-zirconium-niobium alloys using selective laser melting technology. Background Technology

[0002] Titanium alloys refer to various alloys made of titanium and other metals. Currently used titanium alloys, in order to achieve certain performance requirements, contain composite metal materials that inevitably release metal ions into the human body environment, potentially causing negative effects on tissues and organs, leading to inflammation or even disease.

[0003] Currently, titanium-zirconium-niobium alloys are mainly prepared by melting. There are few reports on the preparation of titanium-zirconium-niobium alloys by selective laser melting technology. This is mainly because selective laser melting has problems such as low density and spatter, which make forming difficult. Therefore, it is necessary to explore a process method for forming titanium-zirconium-niobium alloys by selective laser melting technology to expand the processing and preparation routes of titanium-zirconium-niobium alloys, especially high-precision personalized forming of titanium-zirconium-niobium alloys, to meet the needs of the biomedical industry and effectively reduce manufacturing costs. Summary of the Invention

[0004] To address the problems of low density and spatter that occur during selective laser melting in existing technologies, which make it difficult to form titanium-zirconium-niobium alloys, this invention provides a method for preparing titanium-zirconium-niobium alloys using selective laser melting technology.

[0005] This invention is achieved through the following technical solution:

[0006] A method for preparing titanium-zirconium-niobium alloys using selective laser melting technology includes the following steps:

[0007] S1, Weigh the alloy powder. The alloy powder composition by mass ratio is as follows: Zr 39.21%, Nb 39.18%, Fe 0.18%, O 0.134%, N 0.05%, Ti balance;

[0008] S2, fill the top powder chamber with alloy powder and lay the alloy powder on the printing substrate, then clean the printing chamber until the oxygen content in the chamber is less than 0.02%;

[0009] S3, the laser uses a zigzag scanning method to print the alloy powder layer by layer to obtain a titanium-zirconium-niobium alloy sample.

[0010] Preferably, in S1, the particle size of the alloy powder is 10–60 μm.

[0011] Preferably, inert gas is used for cleaning the printing chamber.

[0012] Preferably, the inert gas is argon.

[0013] Preferably, in S2, the height of the alloy powder in the top powder chamber is 2 to 3 times the height of the prepared titanium-zirconium-niobium alloy sample; the thickness of the alloy powder laid on the printing substrate is 20 to 30 μm.

[0014] Preferably, in S2, the printing substrate is a titanium substrate.

[0015] Preferably, in S3, the specific operation of layer-by-layer scanning is as follows:

[0016] S31, the laser spot of the laser is scanned on the printing substrate in a strip scanning manner, and the alloy powder laid on the printing substrate is sintered on the printing substrate to form a pre-planar surface, thus completing the first printing.

[0017] S32, alloy powder is laid on the preparatory plane of the printing substrate, then the height of the printing substrate is lowered, and the laser path of the laser is rotated to sinter the alloy powder on the preparatory plane in a strip scanning manner to complete the second printing;

[0018] S33, repeat S32, until a titanium-zirconium-niobium alloy sample is obtained.

[0019] Preferably, the laser power is 160-320W, the scanning speed is 500-2100mm / s, the scanning spacing is 60-90μm, the laser wavelength is 1060-1080nm, and the output power range is 10-100%.

[0020] Preferably, in S32, the powder layer thickness is 30μm, the height of the printing substrate descent is equal to the layer thickness during printing, and the deflection angle of the laser path between two adjacent printing layers is 60°.

[0021] A product obtained by a method for preparing titanium-zirconium-niobium alloy using selective laser melting technology.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] This invention discloses a method for preparing titanium-zirconium-niobium alloys using selective laser melting (SLM). Zirconium and niobium, elements with minimal toxicity to humans, are used in the composite material process. The rapid solidification characteristic of SLM results in a finer microstructure, while introducing a certain amount of dislocations, significantly improving the strength of the titanium-zirconium-niobium alloy while maintaining good plasticity. This method ensures safety while meeting performance requirements. SLM addresses the issue of low forming density in existing technologies, expanding the processing and preparation routes for titanium-zirconium-niobium alloys. Compared to melting and smelting, the higher instantaneous temperature of the laser in this invention creates a higher temperature gradient within the molten pool, resulting in smaller grain sizes. According to crystal strengthening theory, finer grains strengthen the alloy, increasing strength with decreasing grain size. Furthermore, the formation of dislocations within the grains hinders dislocation activation under stress, thereby enhancing strength.

[0024] Furthermore, the laser power and scanning speed during the printing process affect the prepared product. The volumetric energy density (VED) is calculated as power / (scanning speed * layer thickness * spacing). When VED is too low, the powder melting is poor, resulting in more unmelted powder and less dense powder accumulation. Additionally, unfused pores appear, thus reducing the density. When VED is too high, the heat-affected zone of the molten pool is too deep, and the gas escapes more slowly than the liquid phase solidifies, thus being trapped in the solid phase and forming pores, thereby reducing the density. Attached Figure Description

[0025] Figure 1 This is a flowchart of a method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to the present invention;

[0026] Figure 2 This is a schematic diagram of the interlayer Z-shaped scanning method during selective laser melting in the method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to the present invention;

[0027] Figure 3 This is a schematic diagram of the intralayer strip scanning during selective laser melting in the method for preparing titanium-zirconium-niobium alloy using selective laser melting technology of the present invention;

[0028] Figure 4 This is the EBSD image of the titanium-zirconium-niobium alloy prepared in Example 4;

[0029] Figure 5 This is a comparison of the room temperature tensile curves of the titanium-zirconium-niobium alloy prepared in Example 4 and the titanium-zirconium-niobium alloy prepared by melting and casting. Detailed Implementation

[0030] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.

[0031] This invention discloses a method for preparing titanium-zirconium-niobium alloys using selective laser melting technology, referring to... Figure 1 This includes the following steps:

[0032] S1. Weigh out the alloy powder. The alloy powder composition by mass ratio is as follows: Zr 39.21%, Nb 39.18%, Fe 0.18%, O 0.134%, N 0.05%, Ti balance; the particle size of the alloy powder is 10-60 μm.

[0033] S2, fill the top powder chamber with alloy powder, and then lay the alloy powder on the printing substrate. Clean the printing chamber until the oxygen content inside is below 0.02%. The printing substrate is a titanium substrate, and the height of the alloy powder in the top powder chamber is 2 to 3 times the height of the prepared titanium-zirconium-niobium alloy sample. The thickness of the alloy powder laid on the printing substrate is 20 to 30 μm. The specific operation is as follows:

[0034] S21, constructed using 3D modeling software, is 8×8×8mm. 3 The cube is saved as a .stl file. The model is then sliced ​​and the process parameters are set using 3D printing editing software. The result is saved as a .bjob file and copied to the computer control system of the selective laser melting equipment for sample printing.

[0035] S22, use industrial lint-free paper soaked in 99% anhydrous ethanol to clean the printing chamber, fill the top powder chamber with powder, the height of the powder filling is 2 to 3 times the height of the sample; pre-lay TiZrNb alloy powder on the printing substrate, then wipe the laser lens with alcohol cotton, place the powder recovery box, close the chamber door, and use argon gas to purge until the oxygen content is lower than 0.02%.

[0036] S3, the laser uses a zigzag scanning method (such as...). Figure 2 As shown, alloy powder was printed layer by layer to obtain titanium-zirconium-niobium alloy samples. The laser power ranged from 160 to 320 W, the scanning speed from 500 to 2100 mm / s, the scanning spacing from 60 to 90 μm, the spot diameter from 60 μm, the laser wavelength from 1060 to 1080 nm, and the output power ranged from 10% to 100%.

[0037] The specific operation of layer-by-layer scanning is as follows:

[0038] S31, the laser spot of the laser is scanned on the printing substrate in a strip scanning manner, and the alloy powder laid on the printing substrate is sintered on the printing substrate to form a pre-planar surface, thus completing the first printing.

[0039] S32, alloy powder is laid on the pre-planar surface of the printing substrate, then the height of the printing substrate is lowered, and the laser path of the laser is rotated to sinter the alloy powder on the pre-planar surface in a strip scanning manner (e.g., Figure 3 (As shown), the second printing is completed; the powder layer thickness is 30μm, the height of the printing substrate is lowered equal to the layer thickness during printing; the deflection angle of the laser path between two adjacent printing layers is 60°.

[0040] S33, repeat S32, until a titanium-zirconium-niobium alloy sample is obtained.

[0041] The density of the obtained titanium-zirconium-niobium alloy samples was tested using Archimedes' displacement method, as follows: After printing, the printing substrate and the sample on it were removed. The sample was separated from the titanium substrate by wire cutting, and then polished until the surface was free of scratches and had a mirror finish. After ultrasonic cleaning, the desired product was obtained. After drying, the density was tested. Grinding was done manually with sandpaper, and polishing was performed using damping cloth and silica polishing slurry. Cleaning was done ultrasonically with anhydrous ethanol as the cleaning medium for 3–5 minutes. Drying was carried out in a vacuum drying oven at -0.095 MPa and 100–120°C for 1–2 hours.

[0042] Example 1

[0043] The mass composition of S1,TiZrNb alloy powder is as follows: Zr 39.21%, Nb 39.18%, Fe 0.18%, O 0.134%, N 0.05%, and Ti as the balance; the particle size distribution is D10 16.3 μm, D50 31.5 μm, and D90 56.9 μm.

[0044] S2. An 8×8×8mm³ cube was constructed using 3D modeling software and saved as a .stl file. The model was then sliced ​​and the process parameters were set using 3D printing editing software and saved as a .bjob file. The sample was then copied to the computer control system of the selective laser melting equipment for sample printing.

[0045] S3, Printing Preparation: Clean the printing chamber with industrial lint-free paper soaked in 99% anhydrous ethanol. Fill the top powder chamber with powder to a height twice the height of the sample. Pre-lay a 20μm thick layer of TiZrNb alloy powder on the printing substrate. Then wipe the laser lens with an alcohol swab, place the powder recovery box, close the chamber door, and purge with inert gas until the oxygen content is below 0.02%.

[0046] S4, Printing and Molding: The selective laser melting equipment prints powder according to the designed process documents. The laser spot within each layer scans in a strip scanning manner, sintering a smooth and flat surface. After each layer is printed, the substrate descends to set the layer thickness, and the squeegee evenly spreads the powder from the top powder chamber onto the titanium substrate for the next layer of laser printing. The laser path angle between layers is deflected at 60°, and the plane is sintered in a Z-shaped pattern within each layer. This process is repeated, layer by layer, achieving effective bonding between and within the layers through rapid melting and solidification. The laser power is 160W, the scanning speed is 500mm / s, the scanning spacing is 60μm, and the layer thickness is 30μm.

[0047] S5, Sample processing: After printing, remove the printing substrate and the sample on the substrate. Separate the sample from the titanium substrate by wire cutting. Polish the sample until the surface is free of scratches and has a mirror finish. After ultrasonic cleaning, the desired product can be obtained. After drying, perform density testing.

[0048] The titanium-zirconium-niobium alloy sample prepared in Example 1 has a density of 96.89%, excellent surface quality, and no obvious pores or cracks.

[0049] Example 2

[0050] The difference from Example 1 is that the laser power is 160W and the scanning speed is 1300mm / s.

[0051] The titanium-zirconium-niobium alloy sample prepared in Example 2 has a density of 99.51%, excellent surface quality, and no obvious pores or cracks.

[0052] Example 3

[0053] The difference from Example 1 is that the laser power is 240W and the scanning speed is 2100mm / s.

[0054] The titanium-zirconium-niobium alloy sample prepared in Example 3 has a density of 99.26%, excellent surface quality, and no obvious pores or cracks.

[0055] Example 4

[0056] The difference from Example 1 is that the laser power is 320W and the scanning speed is 1300mm / s.

[0057] The titanium-zirconium-niobium alloy sample prepared in Example 4 has a density of 99.57%, excellent surface quality, and no obvious pores or cracks.

[0058] This invention also discloses a method for preparing titanium-zirconium-niobium alloys using selective laser melting technology. Taking the sample prepared in Example 4 as an example, as... Figure 4As shown, the sample grain size ranges from 5-50 μm, smaller than that of the cast titanium-zirconium-niobium alloy. There is no clear causal relationship between grain size and density. When the powder is completely melted, density is mainly determined by the fluidity of the liquid phase during solidification and the cooling rate. When the fluidity is poor and the cooling rate is too high, the liquid phase's ability to fill pores deteriorates, leading to the formation of voids and a decrease in density. Fluidity and cooling rate are parameter-dependent; in other words, density is affected by process parameters. (Refer to...) Figure 5 The sample has high density, fewer internal pores and defects, and finer grains. Compared with titanium-zirconium-niobium alloys prepared by melting and casting, titanium-zirconium-niobium alloys prepared by selective laser melting have better tensile properties.

[0059] This invention discloses a method for preparing titanium-zirconium-niobium alloys using selective laser melting (SLM). Zirconium and niobium, two elements with minimal toxicity to humans, are used in the composite material process. The rapid solidification characteristic of SLM achieves a finer microstructure while introducing a certain amount of dislocations, significantly improving the strength of the titanium-zirconium-niobium alloy and maintaining good plasticity. This method ensures both performance and safety in use. SLM also addresses the issue of low forming density in existing technologies, expanding the processing and preparation routes for titanium-zirconium-niobium alloys.

[0060] The above description is merely a preferred embodiment of the present invention and is not intended to limit the technical solution of the present invention in any way. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can be modified and replaced in several simple ways, and these modifications and replacements are all within the scope of protection covered by the claims.

Claims

1. A method for preparing titanium-zirconium-niobium alloys using selective laser melting technology, characterized in that, Includes the following steps: S1, Weigh out the alloy powder. The alloy powder composition by mass ratio is as follows: Zr 39.21%, Nb 39.18%, Fe 0.18%, O 0.134%, N 0.05%, Ti balance; S2, fill the top powder chamber with alloy powder and lay the alloy powder on the printing substrate, then clean the printing chamber until the oxygen content in the chamber is below 0.02%; The height of the alloy powder in the top powder chamber is 2 to 3 times the height of the prepared titanium-zirconium-niobium alloy sample; the thickness of the alloy powder laid on the printing substrate is 20 to 30 μm. S3, the laser uses a zigzag scanning method to print the alloy powder layer by layer to obtain a titanium-zirconium-niobium alloy sample; The laser has a laser power of 160~320 W, a scanning speed of 500~2100 mm / s, a scanning spacing of 60~90 μm, a laser wavelength of 1060~1080 nm, and an output power range of 10~100%.

2. The method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to claim 1, characterized in that, In S1, the particle size of the alloy powder is 10~60 μm.

3. The method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to claim 1, characterized in that, In S2, inert gas is used for cleaning the printing chamber.

4. The method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to claim 3, characterized in that, The inert gas is argon.

5. The method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to claim 1, characterized in that, In S2, the printing substrate is a titanium substrate.

6. The method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to claim 1, characterized in that, In S3, the specific operation of layer-by-layer scanning is as follows: S31, the laser spot of the laser is scanned on the printing substrate in a strip scanning manner, and the alloy powder laid on the printing substrate is sintered on the printing substrate to form a pre-planar surface, thus completing the first printing. S32, alloy powder is laid on the preparatory plane of the printing substrate, then the height of the printing substrate is lowered, and the laser path of the laser is rotated to sinter the alloy powder on the preparatory plane in a strip scanning manner to complete the second printing; S33, repeat S32, until a titanium-zirconium-niobium alloy sample is obtained.

7. The method for preparing titanium-zirconium-niobium alloy using selective laser melting technology according to claim 6, characterized in that, In S32, the powder layer thickness is 30μm, and the height to which the printing substrate descends is equal to the layer thickness during printing; the deflection angle of the laser path between two adjacent printing layers is 60°.

8. A product obtained by a method for preparing titanium-zirconium-niobium alloy using selective laser melting technology as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-specific-gravity energetic double-phase high-entropy alloy and preparation method thereof

    CN115369299A

  • High-strength and ductility product Ti-Nb-Zr-Cr-Fe metastable beta titanium alloy for additive manufacturing and preparation method of Ti-Nb-Zr-Cr-Fe metastable beta titanium alloy

    CN115627382A